2021
DOI: 10.1186/s10195-021-00589-5
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of vibration therapy for muscle peak torque and postural control in individuals with anterior cruciate ligament reconstruction: a systematic review and meta-analysis of clinical trials

Abstract: Objective This study aimed to review and summarize the existing evidence on the effectiveness of vibration therapy (VT) in comparison with conventional rehabilitation in anterior cruciate ligament (ACL)-reconstructed patients considering muscle peak torque and postural control. Methods We searched available online databases for relevant studies published up to February 2020. All randomized clinical trials investigating the effect of VT on quadricep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The VIBRO group did not demonstrate signi cant improvements, which aligns with past research suggesting that the e cacy of Whole Body Vibration (WBV) training may hinge on vibration frequency 42,43 . Vibratory stimulation activates the Tonic Vibration Re ex (TVR), characterized by muscle contractions prompted by the excitation of Ia afferents in the muscle spindles 19,20,29 .…”
Section: Discussionsupporting
confidence: 84%
“…The VIBRO group did not demonstrate signi cant improvements, which aligns with past research suggesting that the e cacy of Whole Body Vibration (WBV) training may hinge on vibration frequency 42,43 . Vibratory stimulation activates the Tonic Vibration Re ex (TVR), characterized by muscle contractions prompted by the excitation of Ia afferents in the muscle spindles 19,20,29 .…”
Section: Discussionsupporting
confidence: 84%
“…The vibration may affect the alpha motor neuron, and activate a number of muscle groups, possibly resulting in a better neuromuscular performance. [19,24] However, there is no consensus whether WBV training is beneficial to the functional improvement of patients with PFP, on top of this the pooled outcomes in this study did not support application of WBV training to patients with PFP.…”
Section: Discussionmentioning
confidence: 64%
“…Melo et al , through a recent systematic review, found positive results when vibration-with frequency values of 30 to 35 Hz as set in our study's protocol-was used alone or in association with other types of exercises in older adults with obesity (57). Maghbouli et al reported that CWBV training using a vibration frequency higher than 100 Hz may improve muscle strength and open-eye mediolateral postural control, recommending this technique as a promising approach for decreasing fall risk (58). Additionally, several recent studies found this modality to be an effective stimulus to improve neuromuscular performance and balance in healthy individuals (26), as well as in elderly individuals with neurological disorders (27,32).…”
Section: Discussionmentioning
confidence: 99%